2011
DOI: 10.1111/j.1524-4725.2010.01856.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanocytes and Keratinocytes Transfer Using Sandpaper Technique Combined with Dermabrasion for Stable Vitiligo

Abstract: Transfer of melanocytes and keratinocytes with the sandpaper method is feasible, safe, and effective as treatment for stable vitiligo, although simple dermabrasion is as effective in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 9 publications
1
14
1
Order By: Relevance
“…8 There was a significant increase in the percentage of melanocytes in grafted areas, in comparison with control areas (that were only curetted). 8 Evidence of a discrete increase in the number of melanocytes in the control area was observed, a fact that was confirmed in other studies conducted by Barros et al and Quezada et al 9,10 …”
supporting
confidence: 70%
“…8 There was a significant increase in the percentage of melanocytes in grafted areas, in comparison with control areas (that were only curetted). 8 Evidence of a discrete increase in the number of melanocytes in the control area was observed, a fact that was confirmed in other studies conducted by Barros et al and Quezada et al 9,10 …”
supporting
confidence: 70%
“…52 Dermabrasion Microdermabrasion, first introduced to the United States in 1994, involves the application of a continuous flow of aluminum oxide microcrystals over the skin with simultaneous negative pressure to remove the crystals and skin debris. 54 Another study by Sethi and colleagues 56 showed a success rate of 63% with dermabrasion monotherapy at 6 months after treatment. 53 As outlined above, dermabrasion is a useful tool in the preparation of the recipient site for multiple methods of melanocyte transfer.…”
Section: Epidermal Culturesmentioning
confidence: 98%
“…Despite this strength, its tremendous laboratory requirements and associated costs severely limit the widespread implementation of autologous melanocyte cultures. 54,55 It is hypothesized that microdermabrasion or curettage monotherapy works by activating follicular melanocyte reservoirs, stimulating peripheral epidermal melanocytes, and possibly by activating metabolically inactive melanocytes in vitiliginous patches. 52 Dermabrasion Microdermabrasion, first introduced to the United States in 1994, involves the application of a continuous flow of aluminum oxide microcrystals over the skin with simultaneous negative pressure to remove the crystals and skin debris.…”
Section: Epidermal Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous transplantation of melanocytes and keratinocytes has been attempted to enhance engraftment rates and facilitate procedures (Falabella et al ., 1989; Guerra et al ., 2000; Quezada et al ., 2011), since keratinocytes produce lots of growth factors for melanocyte proliferation and migration. In clinical trial, an easier way of obtaining autologous tissue is also an important consideration.…”
Section: Introductionmentioning
confidence: 99%